Genetic Counseling Training in the Philippines. - Laurino, Mercy Ygona; Padilla, Carmencita David (Journal of Genetic Counseling, 2013)
The recently established Master of Science in Genetic Counseling (MSGC) program serves a vital role in implementing and expanding genetic counseling services in the Philippines. Currently, only eight clinical geneticists practice in the Philippines, a country of approximately 94 million people, which yields a clinical-geneticist-to-population-density ratio of 1:11,750,000. The MSGC program was created to train health care providers to become crucial members of medical genetics teams being formed to meet increasing patient and healthcare provider demands. In 2011, the Board of Regents approved our proposed curriculum at the Department of Pediatrics College of Medicine, University of the Philippines Manila. As we relate how the Philippines began its efforts to implement the program and attempted to overcome the challenges the program faced, we hope we can provide an example to those interested in creating a similar MSGC program in other low-income and middle-income countries.